Effects of land management practices on runoff and soil and nutrient losses in the rainfed agroecosystem of the Beles River Basin, Ethiopia - Yenesew Assaye; Gizaw Desta; Eyayu Molla; Zenebe Adimassu (International Journal of Sediment Research, 2025)
The Beles River Basin is facing severe soil erosion driven by human-induced activities, leading to significant losses of soil organic carbon (SOC) and nutrients (nitrogen (N) and phosphorus (P)). Effective land management practices (LMPs), including mechanical, biological, and agronomic techniques, are potential strategies for mitigating this degradation, but their effectiveness depends on site-specific and agroecological conditions. However, limited information is available on this aspect of the study area. The objective of the current study was to evaluate the effects of LMPs in the warm subhumid lowlands of the Beles River Basin on runoff, soil loss, and sediment-associated losses of SOC, N, and P from agricultural land. Four LMPs (vetiver grass strips (VGS), conservation agriculture (CA), soil bunds (SB), and fanya juu (FJ)) were evaluated via runoff plots arranged in a randomized complete block design (RCBD) with three replicates. Farmer practices were used as a control (C). The experiments, which were performed over three years (2021–2023), generated runoff, soil loss, and nutrient loss data. The three-year mean annual runoff ranged from 58.5 to 407.5 mm, and the soil loss ranged from 4.3 to 45.4 t/ha, whereas the annual rainfall varied between 1,402 mm in 2021, 1,254 mm in 2022, and 1,261 mm in 2023. On average, runoff was reduced by 36%–85%, and soil loss was reduced by 53%–91% in the LMP-treated plots. Additionally, sediment-associated losses of SOC, N, and P were reduced by 55%–90%, 52%–90%, and 28%–72%, respectively. The results revealed significant differences (p < 0.05) among the treatments in terms of reducing runoff, soil loss, and sediment-associated losses of SOC, N, and P. The mean annual runoff and soil loss rates during the study were 407.5, 230.3, 136.3, 59.6, and 58.5 mm and 45.4, 21.5, 11.1, 4.5, and 4.3 t/ha under the control, VGS, CA, SB, and FJ practices, respectively. The highest rates of runoff and soil loss were observed under the control conditions (407.4 mm and 45.4 t/ha). Runoff, soil loss, SOC, and nutrient (N and P) losses were significantly lower (p < 0.05) in the plots treated with FJ and SB than in the other plots. However, CA and VGS also significantly varied (p < 0.05) in reducing runoff, soil, SOC, and nutrient losses over the years. These results highlight the key role of LMPs in warm subhumid lowland rainfed agroecosystems as effective land management techniques for controlling soil and nutrient loss.